Exposing the Causal Effect of Body Mass Index on the Risk of Type 2 Diabetes Mellitus: A Mendelian Randomization Study - Cheng, Liang; Zhuang, He; Ju, Hong; Yang, Shuo; Han, Junwei; Tan, Renjie; Hu, Yang (Frontiers in Genetics, 2019)
Abstract Introduction: High body mass index (BMI) is a positive associated phenotype of type 2 diabetes mellitus (T2DM). Abundant studies have observed this association from clinical perspective. Since the rapid increasement of large numbers of genetic variants from the genome-wide association studies (GWAS), common SNPs of BMI and T2DM were identified as the genetic basis for understanding their associations. Currently, their causality was beginning to blur. Materials and Methods: To classify it, a Mendelian randomisation (MR), using genetic instrumental variables (IVs) to explore the causality of intermediate phenotype and disease, was utilized here to test the effect of BMI on the risk of T2DM. In this article, MR was carried out on GWAS data using 52 independent BMI SNPs as IVs. The pooled odds ratio (OR) of these SNPs was calculated using inverse-variance weighted method for the assessment of 5kg/m2 higher BMI on the risk of T2DM. The leave-one-out validation was conducted to identify the effect of individual SNPs. MR-Egger regression were utilized to detect potential pleiotropic bias of variants. Results: We obtained the high OR (1.470; 95% CI 1.170 to 1.847; P = 0.001), low intercept (0.004, P = 0.661), and small fluctuation of ORs (from -0.039 ((1.412 – 1.470) / 1.470) to 0.075 ((1.568– 1.470) / 1.470)) in leave-one-out validation. Conclusions: We validate the causal effect of high BMI on the risk of T2DM. The low intercept show no pleiotropic bias of IVs. The small alterations of ORs activated by removing individual SNPs shows no single SNP drives our estimate.